Learning shape prior models for object matching - Tingting Jiang; Jurie, Frederic; Schmid, Cordelia (2009 IEEE Conference on Computer Vision and Pattern Recognition, 2009)
The aim of this work is to learn a shape prior model for an object class and to improve shape matching with the learned shape prior. Given images of example instances, we can learn a mean shape of the object class as well as the variations of non-affine and affine transformations separately based on the thin plate spline (TPS) parameterization. Unlike previous methods, for learning, we represent shapes by vector fields instead of features which makes our learning approach general. During shape matching, we inject the shape prior knowledge and make the matching result consistent with the training examples. This is achieved by an extension of the TPS-RPM algorithm which finds a closed form solution for the TPS transformation coherent with the learned transformations. We test our approach by using it to learn shape prior models for all the five object classes in the ETHZ Shape Classes. The results show that the learning accuracy is better than previous work and the learned shape prior models are helpful for object matching in real applications such as object classification.